Penjaminan Dan Peningkatan Mutu Pendidikan di Propinsi Banten - Suharwanto (STIT Muslim Asia Afrika, 2019)
Development and improvement of education quality should be developed and developed in Banten Province with the appropriate system of National Education Standards. School accreditation is a series of quality development process of Education, because in the implementation of Accreditation contains 8 Education Standards Education.